The role of Shaykh Abd Al-Rauf Al-Fansuri on the reconciliation of sufism and shariah of 17th century malay world - Arif, Ridwan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The tension between Sufism and shari'ah, i.e., the conflict of wujudiyyah in Acheh in the 17th century had led Sufi scholars, particularly 'Abd al-Rauf al-Fansuri to seek the convergence between Sufism and shari'ah. Therefore, this study examines the efforts of 'Abd al-Rauf to reconcile Sufism with shari'ah. It examines 'Abd al-Rauf's ap-proaches to reconcile Sufism and shari'ah in the general context as well as in the con-text of the controversial issue, i.e., the doctrine of waḥdat al-wujud. It is a qualitative research which employed content analysis. The result of the study shows that 'Abd al-Rauf had played a significant role in reconciliating Sufism with shari'ah in 17th centu-ry Malay world. The approaches employed by 'Abd al-Rauf helped spread shari'ah sciences and Sufism among Muslims, supporting it by the Qur'an and Sunnah, empha-sizing the significance of stations (al-maqamat), observance of practising shari'ah, and integrating good conducts with Sufism. Meanwhile 'Abd al-Rauf's approach to recon-cile the controversial issue interpreted waḥdat al-wujud in the orthodox sense and crit-icized the extreme approach in Islamic creed ('aqidah).